Ovarian reserve markers and endocrine profile during oral contraception: Is there a link between the degree of ovarian suppression and AMH?. (1st December 2020) - Landersoe, Selma Kloeve; Larsen, Elisabeth Clare; Forman, Julie Lyng; Birch Petersen, Kathrine; Kroman, Mie Stougaard; Frederiksen, Hanne; Juul, Anders; Nøhr, Bugge; Løssl, Kristine; Nielsen, Henriette Svarre; Nyboe Andersen, Anders
Abstract: The ovarian reserve markers anti-Müllerian hormone (AMH) and antral follicle count (AFC) are suppressed in varying degree during the use of combined oral contraceptives (COC). Further, long-term use of COC can mask a condition of premature ovarian insufficiency. A desirable clinical tool that could distinguish true low ovarian reserve markers from COC-induced low levels during use of COC is warranted. The aim of this multicenter study including 235 COC users was to assess whether low age-adjusted AMH levels during COC use were linked to concomitant low levels of LH, FSH, estradiol and androgens – as a potential future tool to differentiate between 'false', COC-induced low AMH levels vs. true low AMH. Study population and methods: In total, 235 COC users from the general population aged 19–40 years were included. AMH, AFC and a reproductive hormonal profile were measured during COC intake. Age-adjusted AMH levels ( Z -scores) were calculated from a comparison group of 983 non-users of COC. Differences in hormonal profile were tested between women with low versus high age-adjusted AMH-quartiles based on non-parametric Wilcoxon rank sum tests. The outcomes of interest were levels of gonadotropins, estradiol and androgens according to the four the age-adjusted AMH quartiles to find out if women with low age-adjusted AMH levels had a stronger gonadotropin suppression compared with women with higher age-adjusted AMH levels. Mean age of COC users was 30.2 years (SD 3.8), median AMH 14 pmol/l (inter-quartile range (IQR) 8.7–23)), median AFC 16 (IQR 11–25). We found no significant differences across the age-adjusted AMH quartiles in either the levels of gonadotropins, estrogens or androgens, respectively. Thus, the degree of suppression of FSH, LH, androgens and estradiol are unlikely to be a useful tool to differentiate between false low and true low ovarian reserve markers during COC use. Presently, there seems to be no alternative to withdrawal of the COC and to re-test the ovarian reserve after 2–3 months. Trial registration Trial no. NCT02785809 (www.clinicaltrials.gov )